2022
DOI: 10.3390/cancers14194721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Concomitant Proton Pump Inhibitors with Pazopanib on Cancer Patients: A Retrospective Analysis

Abstract: The absorption of pazopanib depends on gastric pH. PPIs are frequently prescribed for cancer patients to modify gastric acidity, decreasing pazopanib absorption. The aim of our study was, retrospectively, to investigate the impact of PPIs on the clinical efficacy and safety of pazopanib in a cohort of patients treated in our health center. Of the 147 patients who were included retrospectively, 79 (54%) did not take PPIs concomitantly with pazopanib (cohort 1), while 68 (46%) patients did take PPIs concomitantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Proton pump inhibitors alter the gastrointestinal environment by decreasing gastric acid secretion, consequently influencing drug absorption. 18 Based on the research that reported that patient clinical outcomes deteriorate when oral weakly basic anticancer medications such as tyrosine kinase inhibitors are used in combination with PPIs, 19 , 20 , 21 it appears that complete absorption of palbociclib has been achieved, so it has not shown sufficient therapeutic performance. Even though the type of cancer studied was different from ours, this association was also confirmed from the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Proton pump inhibitors alter the gastrointestinal environment by decreasing gastric acid secretion, consequently influencing drug absorption. 18 Based on the research that reported that patient clinical outcomes deteriorate when oral weakly basic anticancer medications such as tyrosine kinase inhibitors are used in combination with PPIs, 19 , 20 , 21 it appears that complete absorption of palbociclib has been achieved, so it has not shown sufficient therapeutic performance. Even though the type of cancer studied was different from ours, this association was also confirmed from the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have indicated that the concurrent use of PPIs can diminish the antitumor effectiveness or certain drugs like capecitabine and pazopanib ( van Leeuwen et al, 2014 ; Raoul et al, 2023 ). On the other hand, it does not appear to exert a significant influence on the clinical outcomes of patients undergoing treatment with epidermal growth factor receptor (EGFR) inhibitors ( Hilton et al, 2013 ; Kumarakulasinghe et al, 2016 ; Chu et al, 2017 ; Moreau-Bachelard et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%